Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1037/a0034191
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge matters: How children evaluate the reliability of testimony as a process of rational inference.

Abstract: Children's causal learning has been characterized as a rational process, in which children appropriately evaluate evidence from their observations and actions in light of their existing conceptual knowledge. We propose a similar framework for children's selective social learning, concentrating on information learned from others' testimony. We examine how children use their existing conceptual knowledge of the physical and social world to determine the reliability of testimony. We describe existing studies that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
171
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(199 citation statements)
references
References 198 publications
(304 reference statements)
19
171
0
1
Order By: Relevance
“…Our findings signal a more general capacity to integrate social and statistical information into reliability judgments, which develops as toddlers reach better understanding of social and pedagogical cues (see Sobel & Kushnir, 2013). While specific social cues that toddlers may use to make reliability judgments remain subject to further investigation, the present study showed that 18-month-olds generalize new words learned from accurate speakers and extended these results by demonstrating that sensitivity to more sophisticated social cues seem best able to explain the mechanism by which children engage in such inferences.…”
Section: This Finding Corroborates and Extends Work By Brooker Andmentioning
confidence: 99%
“…Our findings signal a more general capacity to integrate social and statistical information into reliability judgments, which develops as toddlers reach better understanding of social and pedagogical cues (see Sobel & Kushnir, 2013). While specific social cues that toddlers may use to make reliability judgments remain subject to further investigation, the present study showed that 18-month-olds generalize new words learned from accurate speakers and extended these results by demonstrating that sensitivity to more sophisticated social cues seem best able to explain the mechanism by which children engage in such inferences.…”
Section: This Finding Corroborates and Extends Work By Brooker Andmentioning
confidence: 99%
“…The present research indicates that young children use social information -specifically, peers' preferences -to inform their relative valuation of options and subsequent preferences. Research on children's learning in social contexts has primarily focused on information that children learn from adults (e.g., Sobel & Kushnir, 2013). However, peers comprise a large and essential component of children's social networks, and understanding what information children are learning from their peers is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have interpreted their results in terms of updating beliefs about informants' knowledge (Pasquini et al, 2007;, theorists have discussed whether epistemic trust is rational (Sobel & Kushnir, 2013), and philosophers have formalized accounts based on reasoning about informants' knowledgeability only (Bovens & Hartmann, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The literature typically explains this development in terms of changes in the ability to monitor who is knowledgeable (Pasquini et al, 2007;). 1 Others have broadly argued that trust is rational (Sobel and Kushnir, 2013). An adjacent literature indicates changes in the ability to reason about deception (Couillard & Woodward, 1999;Mascaro & Sperber, 2009).…”
mentioning
confidence: 99%